A Study to Compare Efficacy of Ultrasound Guided Saphenous Versus Genicular Nerve Block in Osteoarthritis Knee Pain - Mangal Ahlawat; Susheela Taxak; Anju Dahiya; Ashwini Zokarkar; Anushmita Laller; Tarun Yadav (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Background and aim: The most prevalent cause of disability among older persons is osteoarthritis (OA). We compared the efficacy of ultrasound-guided saphenous nerve block (SNB) with genicular nerve block (GNB) in osteoarthritis knee pain.Material and methods: We included 50 patients of either gender, aged 50 years or older, with knee pain from osteoarthritis. The patients were then split into two groups of 25 each. Patients in Group G had a genicular nerve block, and those in Group S received a saphenous nerve block. All patients in either group were given us-guided blocks using 8ml of 0.25% bupivacaine with 1ml (40 mg) of triamcinolone acetonide. Visual analogue scale (VAS) score, patient satisfaction, The Western Ontario and McMaster Universities Index (WOMAC) score (for quality of life), and side effects were assessed to determine the efficacy of the blocks.Results: The mean VAS score was statistically significantly decreased at all-time intervals compared to the baseline score in both groups. WOMAC index was statistically significant (p<0.05) at two and three months but otherwise comparable at all time intervals during the study period. Patient satisfaction was similar in both groups; however, group S exhibited statistically higher satisfaction levels at two months.Conclusions: Ultrasound-guided saphenous nerve block and ultrasound-guided genicular nerve block are functional treatment modalities for OA knee pain before going towards knee surgeries. Both these techniques provide good pain relief and improvement in physical disability to the patients at all-time intervals in our study.